2011
DOI: 10.1002/ejoc.201100232
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Solution‐Phase Synthesis and NMR Studies of Arylopeptoids

Abstract: The development of a highly convenient and efficient protocol for iterative solution-phase synthesis of shorter oligomers of para-and meta-arylopeptoids is described. Peptide coupling methods for accessing longer oligomers were studied: use of the new coupling reagent COMU was found to be the most efficient for creation of the tertiary benzamide bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…We have previously undertaken the first conformational studies of meta ‐ and para ‐arylopeptoids by means of NMR spectroscopy 12a,12c. Intriguingly, we found that the tert ‐butyl and phenyl side chains represented particularly interesting cases because only single, sharp sets of signals were observed in the spectra of meta ‐ and para ‐arylopeptoids carrying these side chains.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously undertaken the first conformational studies of meta ‐ and para ‐arylopeptoids by means of NMR spectroscopy 12a,12c. Intriguingly, we found that the tert ‐butyl and phenyl side chains represented particularly interesting cases because only single, sharp sets of signals were observed in the spectra of meta ‐ and para ‐arylopeptoids carrying these side chains.…”
Section: Resultsmentioning
confidence: 98%
“…at 0 °C to room temp. overnight 12c. We were satisfied to find that this method could be adapted directly to the synthesis of ortho ‐arylopeptoids 2a – 4a and 2b – 4b simply by using 2‐(bromomethyl)benzoyl bromide instead.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations